Written vs. cinematic translation: A case study of culture-bound expressions - Rama Rafat; Mohammed Farghal (Training, Language and Culture)
This study investigates the translation of shared culture-bound expressions in the English version of the Arabic novel The Yacoubian Building and its subtitled film adaptation. A total of 50 expressions found in both the written text (RT) and the cinematic text (CT) are identified and classified into four thematic categories: swearing, idiomatic/proverbial, religious, and address expressions. The analysis examines the use of three translation strategies across these genres: cultural substitution, paraphrase, and literal translation. Cultural substitution is the most frequently used strategy overall and is consistently applied across both genres (RT 32% and CT 30%) and across thematic categories. Literal translation is more frequent in the RT (20%) than in the CT (14%), indicating a greater tolerance for cultural retention in written discourse. Paraphrase, by contrast, is employed more often in the CT (44%) than in the RT (22%), reflecting its practicality in subtitling, where spatial and temporal constraints limit the use of literal or culturally anchored renderings. The findings also reveal that swearing and religious expressions are most often translated using cultural substitution due to their cross-culturally familiar nature, while idiomatic and proverbial expressions are primarily paraphrased because of their deeply embedded linguistic and cultural features. While the translations in both genres are largely successful in conveying meaning, the study recommends expanding the use of cultural substitution in audiovisual contexts to maintain viewer engagement and preserve discursive impact.